Writing for strategic communication industries - Roberts, Jasmine; Ohio State University; BC Open Textbook Project; BCcampus (Ohio State University, 2016)
"Good writing skills are important in today's competitive work environment. This is especially the case for communication-related professions such as public relations, brand communication, journalism, and marketing. Writing for Strategic Communication Industries emphasizes practical application of academic inquiry to help readers improve their writing skills. This book has straightforward chapters that use real-world examples to illustrate key points. It discusses different writing styles and techniques and provides examples of communication materials such as press releases, creative briefs, feature articles, and more. It includes embedded videos of insights from communication professionals, tips on pitching to the media, and a collection of popular sources for further explanation."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on October 24, 2016).
Keywords: Business communication -- Textbooks; Electronic books